Peran Penyuluh Terhadap Kelompok Tani Jagung Panak Jaya Di Desa Kaiya Kecamatan Bolaang Kabupaten Bolaang Mongondow - Sampaleng, Regina Claudia; Timban, Jean Fanny Junita; Memah, Melsje Jelly (Sam Ratulangi University, 2024)
This study aims to describe the role of agricultural extension workers in corn farming in Kaiya Village, Bolaang District, Bolaang Mongondow Regency. This research was conducted from June to July 2023. This study uses 2 types of data, namely primary and secondary data. Sampling using saturated sampling where all members of the population are used as samples. The research sample was the Panak Jaya farmer group consisting of 10 people in Kaiya Village, Bolaang District, Bolaang Mongondow Regency. The data analysis method used in this research is descriptive analysis using a Likert scale. Based on the results of the study which showed the respondent's assessment of the role of the extension worker as a motivator obtained an index of 38.67% for the less involved category, the role of the extension worker as an educator obtained an index of 75.5% for the role category, the role of the extension worker as an organizer obtained an index of 52% for the role category, the role of the extension worker as a communicator was 65.33% for the role category, the role of extension agents as catalysts obtained an index of 62% in the role category and the role of extension agents as advisors obtained an index of 64.67%. category plays a role. In general, the role of extension workers to the Panak Jaya corn farmer group in Kaiya Village, Bolaang District, Bolaang Mondondow Regency was in the role category by obtaining an index of 62.67% in the role category.